1986
DOI: 10.2165/00007256-198603030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Skeletal Muscle Growth

Abstract: Postnatal skeletal muscle growth in humans is generally ascribed to enlargement of existing muscle fibres rather than to cellular proliferation. Some evidence of muscle fibre division or splitting was provided in the nineteenth century. This evidence has more recently been supported by fibres obtained from regenerating muscle, and from muscle which has undergone stress-induced growth. Numerous investigators have reported indirect evidence for exercise-induced hypertrophy and hyperplasia. These findings are lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 49 publications
1
38
0
1
Order By: Relevance
“…Thus, SMA muscle hypoplasia is likely to result from myogenesis defects, independently from and in addition to neuronal death. The fact that in our experimental conditions exercise fails to counteract muscle hypoplasia is consistent with previous data recording that exercise is unable to activate muscle cell proliferation [32].…”
Section: Exercise In Sma: a Milestone In The Treatment Of Neurogenerasupporting
confidence: 93%
“…Thus, SMA muscle hypoplasia is likely to result from myogenesis defects, independently from and in addition to neuronal death. The fact that in our experimental conditions exercise fails to counteract muscle hypoplasia is consistent with previous data recording that exercise is unable to activate muscle cell proliferation [32].…”
Section: Exercise In Sma: a Milestone In The Treatment Of Neurogenerasupporting
confidence: 93%
“…In contrast to these observations, short-term heat acclimation increases the activity of the sweat glands. In short-term heat acclimation trials, Taylor (1986) and Sato et al (1990) observed increased sweat output, increased size of the eccrine sweat glands and increased sensitivity of the sweat glands to methacholine stimulation. These findings confirmed that short and long-term acclimation are mediated by distinct physiological mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…The primary mechanisms involved in muscle mass increase are the proliferative activation (22,23) and myogenic differentiation of mononuclear satellite cells that fuse with the enlarging myofiber, as well as an increased protein synthesis (10,14,30), although some evidence is present that hyperplasia of existing muscle fibers also plays a role in muscle enlargement along with hypertrophy alone (1).…”
Section: Discussionmentioning
confidence: 99%